The governance of decentralised cooperation in collective training systems : a review and conceptualisation - Emmenegger, Patrick [Verfasser]; Graf, Lukas [Verfasser]; Trampusch, Christine [Verfasser] (My University, 2019)
"Collective training systems are based on the cooperation of multiple public and private stakeholders in order to work. However, such cooperation is not self-sustaining and depends, for instance, on public policies, capable intermediary organisations and shared logics of action. In this conceptual paper, we first review the political economy literature on cooperation in collective skill formation and find that it has given insufficient attention to the systematic comparative analysis of cooperation at the decentralised level as well as the actual social practices of cooperation. The paper then develops a multidisciplinary analytical framework that allows future research to examine decentralised cooperation at the regional, sectoral and occupational levels more systematically. This framework is grounded in a synthesis of three strands of empirical research on vocational education and training, namely the comparative political economy literature on governance, corporatism and coordination, institutional labour and societal economics as well as the educational science literature." (Author's abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; S 3.5.4 Sozialpartner; I 2.2.1 Westeuropa; Berufsausbildung; Betriebliche Berufsausbildung; Berufsbildungspolitik; Steuerung; Governance; Korporatismus; Institution; Sozialpartner; Kooperation; Schweiz